Characteristics of Preserving Salafiyah Islamic Boarding School Traditions: Lessons from Indonesia and Malaysia - Munir; Nor, Mohd Roslan Mohd (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
This study aims to understand the characteristics of preserving traditional values of salafiyah Islamic boarding schools (pesantren) in Indonesia and Malaysia. The research method is ethnographic-phenomenological with data collection techniques through observation, documentation, and interviews. This study found that the tradition of salafiyah Islamic boarding school is still preserved in the Islamic boarding school education system, even though they are geographically in different locations and countries. The system they maintain is the charismatic Kyai Kitab as a leadership model, the yellow book as the core curriculum, syawir (muzakarah) as a learning method, and giving oral diplomas as a form of scientific recognition. This study contributes to a deep understanding that traditional Islamic boarding schools (salafiyah) are the original Islamic education of Indonesia and Malaysia which are still the center of classical Islamic tradition preservation.